Inflammatory Biomarkers in AD: Implications for Diagnosis - Kim, Junhyung; Kim, Yong-Ku (Current Alzheimer Research, 2020)
Alzheimer’s disease is the most common form of dementia. Due to the lack of effective interventions, early and accurate diagnosis for new interventions are emphasized. However, significant neuronal loss and neuropathological lesions can damage the brain substantially before diagnosis. With our growing knowledge of the role of neuroinflammation in the pathogenesis of Alzheimer’s disease, inflammatory biomarkers are attracting increasing interest in the context of diagnosis. This review is focused on the use of inflammatory biomarkers detected through neuroimaging, cerebrospinal fluid, and peripheral blood for diagnosing Alzheimer’s disease, and also suggests clinical implications. This review includes the following biomarkers: neuroimaging, various ligands binding to the translocator protein (TSPO); cerebrospinal fluid, soluble triggering receptor expressed on myeloid cells (sTREM2), human cartilage glycoprotein-39 (YKL-40), and monocyte chemoattractant protein 1 (MCP-1), and various biomarkers in peripheral blood. Although accumulating evidence has suggested the potential role of these inflammatory biomarkers in diagnosing AD, there are limitations to their use. However, combining these biomarkers with conventional diagnostic clues such as genotype and amyloid pathology may improve the stratification and selection of patients for targeted early interventions.
Keywords: microglia